2022
DOI: 10.1017/ash.2022.30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the incidence of bacteriuria in female patients before and after implementation of external urinary collection devices

Abstract: External urinary collection devices (ECDs) are increasingly used in female patients, however, their impact on bacteriuria and antimicrobial use is unclear. Comparing the periods before and after the implementation of an ECD use policy, we found an overall decrease in bacteriuria but no significant decrease in trend of monthly rates. Antimicrobial use for genitourinary indications did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Patient and Nurse Satisfaction 8 22,24,26,28,30,35,38,68 Satisfaction was high. Studies indicated good patient and caregiver satisfaction with home, outpatient community, and hospice care use of PureWick.…”
Section: More Data Neededmentioning
confidence: 98%
“…Patient and Nurse Satisfaction 8 22,24,26,28,30,35,38,68 Satisfaction was high. Studies indicated good patient and caregiver satisfaction with home, outpatient community, and hospice care use of PureWick.…”
Section: More Data Neededmentioning
confidence: 98%